(untitled) (Scientia Agropecuaria, 2025)
Land-use change in the Central Andes of Peru has led to the widespread conversion of tropical montane forests, significantly reducing their carbon storage capacity. This study estimated aboveground and soil carbon stocks across a disturbance gradient: croplands (C), agroforestry systems (AF), regenerating montane forests (BMR), and conserved montane forests (BMC). Using destructive and non-destructive sampling, 61 plots (0.1 ha each) were assessed, measuring live and dead aboveground biomass, fine roots, and soil organic carbon down to 1 meter. Results show that BMC had the highest total carbon stock (575.33 ± 215.4 Mg C ha⁻¹), followed by BMR (386.53 ± 186.6), AF (276.69 ± 172.5), and C (205.14 ± 114.03). Soil organic carbon was the dominant carbon pool across all land uses, contributing between 93% (in croplands) and 62% (in conserved forests) of total carbon, highlighting its central role in carbon dynamics. Carbon stocks were significantly associated with vegetation structural attributes (basal area, diameter at breast height, canopy cover) and soil properties (texture, cation exchange capacity, organic matter content). Trees with diameter at breast height ≥ 30 cm contributed over 50% of aboveground carbon, underlining their importance in biomass carbon storage. These findings reveal a clear gradient of loss in the ecosystem service of carbon storage, driven by land-use intensification and the simplification of forest structure. However, they also demonstrate that the recovery of degraded forests and the implementation of agroforestry systems are viable strategies to reduce the loss of ecosystem functions and contribute meaningfully to climate change mitigation.